Sistem Pendukung Keputusan Menentukan Benih Padi Terbaik Menggunakan Metode TOPSIS - Rahel Nita Trides Siahaan; Irfan Sudahri Damanik; M. Fauzan (LPPM STIKOM Tunas Bangsa, 2021)
Farmers are engaged in agriculture in a way to manage land to grow and maintain plants, farmers play an important role in Indonesia. The majority of the population is the majority of farmers and is very dependent on rice. But there are some communities that are very difficult to determine which rice seeds are good and quality to be replanted. The best rice seeds are factors that influence the business productivity of farmers. Most of the farmers have not fully understood the various types of rice seeds and are still looking for solutions to choose quality rice seeds, of course. To use these problems a Decision Support System is needed which is expected to solve these problems. The author chooses the TOPSIS method which will provide information while helping farmers in making decisions about the rice seeds they will use. By applying the TOPSIS Method can produce the right decision to choose the best rice seeds.